2020
DOI: 10.1002/mnfr.201900949
|View full text |Cite
|
Sign up to set email alerts
|

Xanthophyll β‐Cryptoxanthin Inhibits Highly Refined Carbohydrate Diet–Promoted Hepatocellular Carcinoma Progression in Mice

Abstract: Scope: -Cryptoxanthin (BCX) can be cleaved by both -carotene 15,15′-oxygenase (BCO1) and -carotene 9′,10′-oxygenase (BCO2), generating biological active vitamin A and apocarotenoids. We examined whether BCX feeding could inhibit diethylnitrosamine (DEN)-initiated, highly refined carbohydrate diet (HRCD)-promoted hepatocellular carcinoma (HCC) development, dependent or independent of BCO1/BCO2 activity. Methods and results: Two-week-old male wild-type (WT) and BCO1 −/− /BCO2 −/− double knockout (DKO) mice are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
(58 reference statements)
3
12
0
Order By: Relevance
“…Since apo-carotenoid, metabolites of BCO2 can be further cleaved by BCO1 to generating vitamin A (30), our findings suggest that BCX itself exerted a protective effect. This is corroborated by our recent study with BCX supplementation in fatty liver and hepatocellular carcinoma in mice, in which BCX was effective in preventing those outcomes (12,15,16,31). By contrast, in the study by Amengual et al (17), severe liver steatosis was developed in BCO2-KO mice at ~3 months (13 weeks) of age after feeding a vitamin A-deficient purified diet (based on AIN-93G formulation) supplemented with 50 mg/kg lutein or 50 mg/kg zeaxanthin.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Since apo-carotenoid, metabolites of BCO2 can be further cleaved by BCO1 to generating vitamin A (30), our findings suggest that BCX itself exerted a protective effect. This is corroborated by our recent study with BCX supplementation in fatty liver and hepatocellular carcinoma in mice, in which BCX was effective in preventing those outcomes (12,15,16,31). By contrast, in the study by Amengual et al (17), severe liver steatosis was developed in BCO2-KO mice at ~3 months (13 weeks) of age after feeding a vitamin A-deficient purified diet (based on AIN-93G formulation) supplemented with 50 mg/kg lutein or 50 mg/kg zeaxanthin.…”
Section: Discussionsupporting
confidence: 78%
“…Second, the mean liver BCX concentration in the mice supplemented with 10 mg BCX/kg diet in this study (0.64 nmol/g) was comparable to that reported in human livers (0.66 nmol/g) (34). Furthermore, the BCX dose used in the present study, which was equivalent to daily human consumption of 0.87 mg of BCX, can be obtained from dietary citrus fruits, such as consuming three raw tangerines daily (15,16,31).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is mostly present in citrus fruits, although it is also found in corn, peas, and other yellow animal products (16,39). β-cryptoxanthin has been demonstrated in animal experiments to have preventative and inhibitory effects on a number of malignancies, including colon cancer (40), gastric cancer (41), lung cancer (42)(43)(44), bladder cancer (45), and liver cancer (46) through a variety of molecular mechanisms. It has been demonstrated that β-cryptoxanthin in combination with oxaliplatin dramatically increased the apoptosis of colon cancer cells in vitro and in vivo, indicating anti-tumor and therapeutic actions on CRC (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another paper demonstrated that dietary BCX for 24 weeks suppressed the progression of chemically and highly refined carbohydrate diet-induced hepatocellular carcinoma in mice. The mechanisms underlying this effect involved an increase in p53 acetylation, with the subsequent induction of apoptosis and the reduction in HIF-1α and its down-stream targets, MMP-2 and MMP-9 [370].…”
Section: In Vivo Studiesmentioning
confidence: 99%